Proceedings of the 2003 Workshop on Location-Aware Computing - Hazas, Mike; Scott, James; Krumm, John (Proceedings of the 2003 Workshop on Location-aware computing (Part of UbiComp 2003), 2003)
Determining the location of people and objects has been the focus of much research inubiquitous computing. Many location sensing technologies have been devised, resulting in systems which perform sensing using diverse physical media, such as infrared light, ultrasound, electromagnetic signals, ground reaction force, physical/electrical contact, and visible light. Naturally, these systems have an equally diverse set of properties; each implementation has its own level of accuracy, update rate, infrastructure cost, deployment diﬃculty, robustness, and capacity for privacy guarantees. Location-aware applications are numerous. Examples include portable memory aids, conference assistants, environmental resource discovery and control, support systems for the elderly, tour guides, augmented reality, mobile desktop control, 3D mice, and virtual buttons. Each demands diﬀerent levels of service from the supporting systems, for example in terms of location accuracy and update rate. There has also been a recent focus on location-aware “platforms,” which link data-gathering systems and the data-consuming applications in a ﬂexible manner. Such work includes location representation, sensor fusion to combine location data from many sources, and software frameworks supporting the distributed nature of location-aware computing. Such abstractions are essential for the interoperability, usability and development of location-aware systems and applications. Finally, location-aware computing includes many issues related to the user experience, such as privacy preservation and its associated legal and ethical implications, the questions of usability and user acceptance, and the need for security in the determination and transfer of personal data.